Transformational Leadership Model in Islamic Education - Ismail Anshari; Tihalimah Tihalimah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
The transformational leadership leads its human resource into its elightment sensitivity, organisational development, collective vision, leadership delegation, and developing organisational culture which is a must in organisational restructure scheme. This leadership model would be able to accelerate the awareness of its followers by promoting productive ideas, a synergical relationship, responsibility, educational concern and collective expcetations. The transformational leadership leaders are those visionary and able to identify changes and transformation into organisations. In addition, they will be able to promote organisational changes  and motivate creative and innovative individual employees. Furthermore, they also build strong team work, promote the positive working culture and maintain responsibility.